Caso de Poesia (Antônio Carlos de Brito, vulgo Cacaso) - Ferreira, Sandra Aparecida [UNESP] (My University, 2014)
This paper deals with characteristically anti-authoritarian aspects of Antônio Carlos de Brito’s work, alias Cacaso (1944-1987). It aims to provide evidence on his peculiar poetry writing exercise, which incorporates political and aesthetic tensions into its own language, rather than just refer to them. By anchoring in a poetics of everyday life and by being engaged in a dialogue with Brazilian literary tradition, Cacaso manages image, tone and emotion in order to instantly illuminate the impasses of his generation.

Este artigo verifica aspectos da dicção anti-autoritária na obra de Antônio Carlos de Brito, o Cacaso (1944-1987). Tem por objetivo evidenciar um exercício poético que incorpora tensões políticas e estéticas à sua própria linguagem, ao invés de apenas referi-las. Ancorado em uma poética do cotidiano e dialogando com a tradição literária brasileira, Cacaso maneja imagem, tom e emoção para iluminar, instantaneamente, os impasses de sua geração.
A case of poetry (Antônio Carlos de Brito, Alias Cacaso)
Keywords: Brazilian literature; Marginal poetry; 60s/70s Generation; Cacaso; Literatura brasileira; Poesia marginal; Geração de 60/70; Cacaso